2017
DOI: 10.18203/2349-3933.ijam20170095
|View full text |Cite
|
Sign up to set email alerts
|

Role of helical CT and MRI in the evaluation of spinal dysraphism

Abstract: Background: Spinal dysraphism is a complex congenital anomaly involving the spine and spinal cord. Some lesions seldom require imaging. The aim was to study the usefulness of helical CT and MRI in the evaluation of various presentation of spinal dysraphism, to identify, characterize the lesions and its association with other anomalies which helps in giving an accurate diagnosis based on specific imaging findings.Methods: Seventy patients including 33 males and 37 females’ age ranging from 1year to 30 years cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Among closed SDs, spinal Lipoma was the most common. This is in accordance with studies by Kumaran et al [8] and Hosagavi et al [9] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among closed SDs, spinal Lipoma was the most common. This is in accordance with studies by Kumaran et al [8] and Hosagavi et al [9] .…”
Section: Discussionsupporting
confidence: 94%
“…Most of the patients were females. Irwin et al 7 [] , Kumaran et al [8] and Hosagavi et al [9] also had reported a strong female preponderance in their respective studies.…”
Section: Discussionmentioning
confidence: 98%